Discovery and characterization of nutritionally regulated genes associated with muscle growth in Atlantic salmon - Bower, Neil I.; Johnston, Ian Alistair (Physiological Genomics, 2010)
Bower NI, Johnston IA. Discovery and characterization of nutritionally regulated genes associated with muscle growth in Atlantic salmon. Physiol Genomics 42A: 114-130, 2010. First published July 27, 2010; doi:10.1152/physiolgenomics.00065.2010.-A genomics approach was used to identify nutritionally regulated genes involved in growth of fast skeletal muscle in Atlantic salmon (Salmo salar L.). Forward and reverse subtractive cDNA libraries were prepared comparing fish with zero growth rates to fish growing rapidly. We produced 7,420 ESTs and assembled them into nonredundant clusters prior to annotation. Contigs representing 40 potentially unrecognized nutritionally responsive candidate genes were identified. Twenty-three of the subtractive library candidates were also differentially regulated by nutritional state in an independent fasting-refeeding experiment and their expression placed in the context of 26 genes with established roles in muscle growth regulation. The expression of these genes was also determined during the maturation of a primary myocyte culture, identifying 13 candidates from the subtractive cDNA libraries with putative roles in the myogenic program. During early stages of refeeding DNAJA4, HSPA1B, HSP90A, and CHAC1 expression increased, indicating activation of unfolded protein response pathways. Four genes were considered inhibitory to myogenesis based on their in vivo and in vitro expression profiles (CEBPD, ASB2, HSP30, novel transcript GE623928). Other genes showed increased expression with feeding and highest in vitro expression during the proliferative phase of the culture (FOXD1, DRG1) or as cells differentiated (SMYD1, RTN1, MID1IP1, HSP90A, novel transcript GE617747). The genes identified were associated with chromatin modification (SMYD1, RTN1), microtubule stabilization (MID1IP1), cell cycle regulation (FOXD1, CEBPD, DRG1), and negative regulation of signaling (ASB2) and may play a role in the stimulation of myogenesis during the transition from a catabolic to anabolic state in ...